Reaction Speed Training Sensor Aids Development for Taekwondo - Siregar, Zulfikar; Soegiyanto, Soegiyanto; Rustiadi, Tri (Journal of Physical Education and Sports, 2021)
Modern developed countries have used technology in the field of sports, and as a result, they frequently outperform their competitors. Some countries have yet to incorporate technology in sports since it is expensive, therefore they continue to rely on traditional techniques. The purpose of this study is to create a product that can be used for kick reaction speed training in taekwondo sports. This study is a development study that employs ten stages of development processes. In this study, data was gathered using product validation questionnaires, respondent questionnaires, interviews, and documentation. In this study, descriptive percentages were utilized as a data analysis technique. The findings of this study are in the form of a sensor tool based on a smartphone application for training kick reaction speed in the Taekwondo martial arts branch. Research result on a small-scale trial involving 10 athletes yielded a percentage score of 73%. A large-scale study including 45 athletes and 4 coaches yielded a percentage score of 92 percent athletes and 92 percent coaches, earning them the "extremely feasible" category. Conclusion this study resulted in a smartphone application -based sensor tool product with a function to train kick reaction speed in the taekwondo martial arts branch, which has a good tool effectiveness and gets a positive response from both coaches and athletes.